Influence of food and temperature on growth performance and maturation of Lymnaea peregra (Muller) (Gastropoda: Pulmonata: Lymnaeidae) under laboratory conditions (University Journal of Zoology, Rajshahi University, 2007)
Key words: Growth performance; food and temperature; Lymnaea peregra Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 1-6